Roadkill of wild vertebrates along the GO-060 road between Goiânia and Iporá, Goiás State, Brazil - doi: 10.4025/actascibiolsci.v32i3.4752 - Hélida Ferreira da Cunha; Fabiane Geralda Alves Moreira; Silvania de Sousa Silva (Acta Scientiarum. Biological Sciences, 2010)
Roadkill of wild vertebrates along GO-060, Brazil. Roads represent an old and constant cause of accidental death of wildlife. From May 2004 to November 2005, we recorded the roadkills of vertebrates in the GO-060 road between Goiânia and Iporá. For each road-killed animal we wrote down the species and location along the road. We found 308 animals road-killed from at least 25 vertebrate species: 86% mammals, 11% birds and 3% reptiles. Tamandua tetradactyla, Cerdocyon thous and Myrmecophaga tridactyla were, in decreasing order, the species with the largest number of road-killed individuals. Among mammals, the number of road-killed individuals was not related to species weight. The number of species and road-killed animals was constant throughout the 17 months of the research. The average frequency of animal roadkills in the dry season (April to September) is slightly higher than the frequency in the rainy season (October to March). The average frequency of species victim to accidents, however, is constant throughout the dry and rainy seasons. The incidence of species and individuals of road-killed animals per 10 km was not influenced by the number of forest fragments along the sides of the road. We suggest that speed reducers could decrease the number of animals killed on the road.